Calcium homeostasis in second trimester fetuses. Issue 8 (August 1986) - Moniz, C F; Nicolaides, K H; Tzannatos, C; Rodeck, C H
Abstract : The concentrations of ionised calcium ions (Ca++), total calcium, parathyroid hormone, pH, total protein, albumin, sodium, and potassium were measured in paired fetal and maternal blood from pregnancies at 15 to 24 weeks' gestation. Pure fetal blood samples were obtained fetoscopically. The concentrations of fetal ionised calcium ions (n = 26); mean (SD) 1.33 (0.12) mmol/l (5.32 (0.48) mg/100 ml) and those of parathyroid hormone (n = 9); 68 (19) pmol/l (58 (16) micrograms/100 ml) were significantly higher than those of the mothers: 1.18 (0.09) mmol/l (4.7 (0.4) mg/100 ml), and 40 pmol/l (less than 34 micrograms/100 ml), respectively. There was no difference between measured fetal and maternal total calcium, pH, and electrolytes. The fetal total protein and albumin concentrations increased with gestation but were always lower than the equivalent maternal values. The calculated total calcium was 0.23-0.45 mmol/l (0.9-1.8 mg/100 ml) higher in the fetal than in maternal blood from the same pregnancy. There were no fetal arteriovenous differences in ionised calcium ions despite higher venous pH.